Stigma Masyarakat Tentang Gangguan Mental Emosional: (Studi di Kelurahan Delima Kecamatan Tampan Pekanbaru) - Widiyanto, Juli; Anisah, Resti (As-Shiha: Jurnal Kesehatan, 2021)
Stigma is a negative label attached to the body of someone who is paid by the public and influenced by the environment. Very often many people equate people with mental disorders with mental emotional disorders. This research aims to describe the stigma against with mental emotional disorders clients in Delima Village Tampan District Pekanbaru. This research used descriptive design method. The Population investigated 4502 people and a sample of 105 respondents was taken using stratified random sampling technique. The research instrument used a quistionnaire. Data analysis was used with SPSS program in the form univariate analysis. Based on the resluts of the study, it was found that the community’s stigma against people with mental emotional disorders was 50 out of 105 respondents.